Topographical analysis of stimulus-related and response-related electrical scalp activity and interhemispheric dynamics in normal humans - Braun, Claude M.J; Villeneuve, Loı̈c; Gruzelier, John H (International journal of psychophysiology, 2002)
It is believed that reaction time estimates of interhemispheric relay (IHR) time or accuracy cost reflect motor relay and that visual evoked response potential (ERP) estimates reflect visual relay ( Brown and Jeeves, 1993). If this is so, then response-related ERP estimates of IHR might be expected to correlate more with reaction time (RT) estimates of IHR than visual ERPs do, and the former ought to interact with the latter. A simple reaction time experiment (Poffenberger paradigm) was carried out with an 18-electrode montage on 10 normal subjects to investigate visual and motor interhemispheric relay effects and their interrelation. Three components in stimulus-synchronized and three other components in response-synchronized averaged signals were analyzed. Latencies and amplitudes of these components were studied as a function of the visual field stimulated and the hand required to respond. Effects interpretable as interhemispheric relay effects were observed in stimulus-related as well as response-related components. Few interhemispheric relay effect estimates in stimulus-related and response-related electrical scalp potentials were related to behavioral estimates of interhemispheric relay effects (derived from reaction times and omission errors). The spatiotemporal distributions of the electrical interhemispheric relay effects differed in stimulus and response-related components and they were statistically unrelated. We conclude that sensory interhemispheric relay may be picked up with stimulus-synchronized ERPs whereas motor interhemispheric relay effects may be measurable with response-related ERPs in normal humans. However, this proposal ought to be tested with callosotomized subjects.